2014
DOI: 10.1007/s00213-014-3845-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of circadian disruption on methamphetamine consumption in methamphetamine-exposed rats

Abstract: Rationale A substantial number of clinical studies indicate associations between sleep abnormalities and drug abuse; however, the role played by the circadian system in the development of addiction is largely unknown. Objective The aim of this study was to examine the effects of experimentally induced chronic jet lag on methamphetamine consumption in a rat model of methamphetamine drinking. Methods Male Sprague-Dawley rats (n=32) were housed in running wheel cages in a 12:12 light:dark cycle. One group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Furthermore, people with perturbations of the circadian system [e.g., shift-workers, people experiencing frequent jet-lags; ( 10 )], or animal models with disruptions of the body clock [e.g., chronic jet-lag exposure; ( 11 )] show an increase of drug intake (e.g., psychostimulants). For example, shift-workers use methamphetamine to avoid sleepiness and perform tasks accurately during their working hours.…”
Section: The Clock On Drugsmentioning
confidence: 99%
“…Furthermore, people with perturbations of the circadian system [e.g., shift-workers, people experiencing frequent jet-lags; ( 10 )], or animal models with disruptions of the body clock [e.g., chronic jet-lag exposure; ( 11 )] show an increase of drug intake (e.g., psychostimulants). For example, shift-workers use methamphetamine to avoid sleepiness and perform tasks accurately during their working hours.…”
Section: The Clock On Drugsmentioning
confidence: 99%
“…These data suggest that MA effects on circadian rhythm may also be protective against MA consumption (Olsen et al, 2013 ). We have not examined whether circadian rhythm disturbance might alter MA intake, but a recent study by Doyle et al ( 2015 ) reported that MA consumption was increased in phase-shifted rats that had a history of MA use.…”
Section: Development Of An Animal Model Of Genetic Risk For Ma Intakementioning
confidence: 99%
“…Second, circadian rhythm disorders increase susceptibility to addiction. Repeated light/dark conversion can increase alcohol intake (36) and the preference for MA (37) in pre-exposure-treated rats. In humans, epidemiological studies reported that shift work or jet lag was associated with increased smoking and alcohol consumption (38,39).…”
Section: Analysis Of Dmr Data Inferred the Role Of The Circadian Entrmentioning
confidence: 98%